STRATEGI ADAPTIF GURU KELAS DALAM MENGEMBANGKAN EFIKASI PADA PENYELENGGARAAN SEKOLAH INKLUSI TANPA GURU PENDAMPING KHUSUS - Mardianti Dwiardhany; Liftiah Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of inclusive education in Indonesia continues to face a significant structural challenge, namely the acute shortage of Special Assistance Teachers (GPK). This condition places classroom teachers as the frontline of inclusive services without adequate professional support, forcing them to develop their own strategies to maintain teaching effectiveness. This study aims to explore the adaptive strategies employed by classroom teachers to develop and sustain their self-efficacy in managing inclusive classes without GPK. A qualitative phenomenological approach was adopted, selecting six classroom teachers from public elementary schools in three schools of Blora Central Java through purposive sampling. Data collection involved semi-structured in-depth interviews and participatory observation, analyzed using the thematic analysis framework of Braun and Clarke. The findings reveal five main adaptive strategies: simplification and concrete visualization of instructional materials, flexible learning management through time modification, spontaneous instructional improvisation to address challenging behaviors, extensive informal collaboration with parents and colleagues, and self-reflective practices as a continuous learning mechanism. These strategies operate as a self-driven support system that sustains teacher self-efficacy, even without formal GPK assistance. This study concludes that the sustainability of inclusive education heavily relies on the development of a systematic support ecosystem, including continuous training and mental health services for teachers.